Melanoma antigens and related immunological markers. (July 2017) - Pitcovski, Jacob; Shahar, Ehud; Aizenshtein, Elina; Gorodetsky, Raphael
Abstract: Melanoma is a highly lethal cancer deriving from transformed dermal melanocytes. Early diagnosed primary melanoma may be curable, but the cure-rate of more advanced stages is limited, with high mortality rate. With the progression of the tumor, the melanocytes overexpress intracellular or cell-surface molecules, including ectopic normal and tumor-specific proteins. Some of these induce a specific immune response by T and B lymphocytes. Antibodies raised against melanoma antigens were proposed for differential disease diagnosis, staging, prognosis and evaluation of treatment efficiency. Nevertheless, treatments based on stimulation of specific anti-melanoma immune responses have had only limited success. It seems that efficient immunotherapy should become more feasible pending on finding new adequate antigens to target. New insights into immune regulation of the tumor microenvironment and its progression may help the development of more successful treatments. We present here up-to-date information on known major melanoma-associated antigens, which could serve as tools for diagnosis as well as for clinical immunotherapy. This approach with promising results for treating some other selected malignancies is still experimental with a very limited success in melanoma. The development of new immune modulators of the tumor microenvironment and neo-antigens may be additional promising directions and may open new opportunities for the immunotherapy of melanoma.